Spatiotemporal Developmental Upregulation of Prestin Correlates With the Severity and Location of Cyclodextrin-Induced Outer Hair Cell Loss and Hearing Loss - Ding, Dalian; Jiang, Haiyan; Manohar, Senthilvelan; Liu, Xiaopeng; Li, Li; Chen, Guang-Di; Salvi, Richard (Frontiers in Cell and Developmental Biology, 2021)
HPβCD (2-hyroxypropyl-beta-cyclodextrin is being used to treat Niemann-Pick C1, a fatal neurodegenerative disease caused by abnormal cholesterol metabolism. HPβCD slows disease progression, but unfortunately causes severe, rapid onset hearing loss by destroying the outer hair cells (OHC). HPβCD-induced damage is believed to be related to the expression of prestin appears in OHCs. Because, prestin is postnatally upregulated from the cochlear base towards the apex, we hypothesized that HPβCD ototoxicity would spread from the high-frequency base towards the low-frequency apex of the cochlea. Consistent with this hypothesis, cochlear hearing impairments and OHC loss rapidly spread from the high-frequency base towards the low-frequency apex of the cochlea when HPβCD administration shifted from postnatal day 3 (P3) to P28. HPβCD-induced histopathologies were initially confined to the OHCs, but between 4- and 6-weeks, there was an unexpected, rapid and massive expansion of the lesion to include most inner hair cells (IHC), pillar cells, peripheral auditory nerve fibers, and spiral ganglion neurons at location where OHCs were missing. The rapid onset of HPβCD-ototoxicity is initially triggered by the spatiotemporal upregulation of prestin in OHCs which is followed four to six weeks later by a second massive wave of degeneration that includes the IHC, pillar cells auditory nerve fibers and spiral ganglion neurons resulting in profound, irreversible hearing loss.